Pengaruh Model Team Assisted Indvidualization (TAI) Terhadap hasil Belajar IPA Siswa Kelas IV SDN 08 Nan Sabaris - Dasmita, Dasmita; Lelfita, Lelfita (Jurnal Pendidikan Nasional, 2021)
The purpose of this study was to determine whether there was an Influence of the Team Assisted Individualization (TAI) Learning Model on Science Learning Outcomes for Class IV SDN 08 Nan Sabaris. This type of research is quasi-experimental using a comparisson's static group design model. The population of the study was the fourthgrade students at SDN 08 Nan Sabaris and the fourth grade students at SDN 12 Nan ​​Sabaris. Sampling of research is saturated sampling technique. So the sample used is class IV SDN 08 Nan Sabaris and class IV SDN12 Nan ​​Sabaris. Data collection techniques were tests. Data analysis techniques used were normality, homogeneity, and hypothesis testing. The results of the final test of the two sample classes showed that the average value in the experimental class was 81.17 with the highest score of 100 and the lowest being 50, and the final test score of the control class was 72.47 with the highest score of 100 and the lowest 37. After testing the hypothesis using t test, obtained the value of tcount = 2.63 while the value of ttable = 2.39. So it can be concluded that there is an effect of the Team Assisted Individualization (TAI) model on student learning outcomes in science learning IPA for Class IV SDN 08 Nan Sabaris